Teachers Reflections on Teaching Mathematics in English: A Consideration for Developing ESP Course - Atin Kurniawati (ELE Reviews: English Language Education Reviews, 2021)
This study aims at investigating the difficulties faced by mathematics teachers in delivering learning materials in English, the strategies carried out by the teachers to overcome their problems, and its implication for ESP design. Conducted in a private school in Surakarta, which uses the Cambridge curriculum, this study involved five mathematics teachers. The data were collected by interview to elicit detailed information. Then, the data were analyzed using the interactive analysis method. Based on the study, the teachers faced several difficulties, namely vocabulary mastery, pronunciation, grammar mastery, and speaking fluency. The teacher's strategies to cope with the difficulties were improving English skills by learning from reference books and other sources, printed or online, and collaborating with peer teachers. They also used an online platform to assist their learning as well as prepare the learning media. It implied that ESP design for mathematics teachers needed to cover four aspects: vocabulary mastery, pronunciation, grammar mastery, and speaking fluency. Several platforms could be utilized to design the ESP course, including the platforms that supported the linguistic aspects and mathematical knowledge.